Trade, education, and the shrinking middle class - Emily Blanchard; Gerald Willmann (Kiel Institute for the World Economy (IfW), 2013)
We develop a new model of trade in which educational institutions drive comparative advantage and determine the distribution of human capital within and across countries. Our framework exploits a multiplicity of sectors and the continuous support of human capital choices to demonstrate that freer trade can induce crowding out of the middle occupations towards the skill acquisition extremes in one country, and simultaneous expansion of middle-income industries in another. Individual gains from trade may be non-monotonic in workers' ability, and middle ability agents can lose the most from trade liberalization. Comparing trade and education policy, we find that targeted education subsidies are more effective than tariffs as a means to preserve middle class jobs, while uniform educational subsidies have no effect.
Keywords: F11; F13; F15; F16; 330; Trade and Education Policy; Skill Acquisition; Education; Income Distribution